1995
DOI: 10.2307/3284059
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Innate Peripheral Blood Eosinophilia Fails to Augment Irradiated Cercarial Vaccine-Induced Resistance to Schistosoma mansoni in IL-5 Transgenic Mice

Abstract: Numerous factors contribute to host resistance to infection with Schistosoma mansoni. Although several studies have investigated the eosinophil as an effector cell of protective responses, its true role remains unclear. In vitro, human, but not mouse, eosinophils can kill schistosomula. Studies on schistosome infection susceptibility in naive or vaccinated eosinophil-deficient mice have yielded conflicting results. Using the gamma-irradiated cercariae (irr-cerc) model, we vaccinated interleukin (IL)-5 transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Meanwhile, worm recovery of Mesocestoides corti from IL-5-Tg mice was not signi®cantly dierent from that from nontransgenic mice (Strath et al 1992). Similarly, IL-5-Tg mice vaccinated with irradiated S. mansoni cercariae failed to produce protective immunity to a challenge infection with normal cercariae, as found in C3H/HeN control mice (Freeman et al 1995). More recently, similar ®ndings were obtained from IL-5-Tg mice primarily infected with T. canis or from those vaccinated with excretory and secretory antigens and then challenged with the same parasite (Sugane et al 1996).…”
Section: Discussionsupporting
confidence: 58%
“…Meanwhile, worm recovery of Mesocestoides corti from IL-5-Tg mice was not signi®cantly dierent from that from nontransgenic mice (Strath et al 1992). Similarly, IL-5-Tg mice vaccinated with irradiated S. mansoni cercariae failed to produce protective immunity to a challenge infection with normal cercariae, as found in C3H/HeN control mice (Freeman et al 1995). More recently, similar ®ndings were obtained from IL-5-Tg mice primarily infected with T. canis or from those vaccinated with excretory and secretory antigens and then challenged with the same parasite (Sugane et al 1996).…”
Section: Discussionsupporting
confidence: 58%
“…Nevertheless, only a few transgenic animal models have been used to investigate the involvement of cytokines in immunity to parasites. Considering the helminth S. mansoni , the role of eosinophils as effector cells during infection has been analysed using IL‐5 transgenic mice (30) as has the consequence of IL‐4‐overexpression in the granulomatous reaction (31).…”
Section: Discussionmentioning
confidence: 99%
“…25]. However, the role of eosin ophils as an anti-parasite killer cell in vivo remains con troversial [10,11,17,[26][27][28], in spite of the many demon strations that these cells can be potently cytotoxic [1,3,4,8,29], N. brasiliensis has been widely used as a laboratory model in studies of Th2-type immune responses against intestinal helminths. Infection with this parasite is char acterized by high eosinophilia, and experiments using anti-IL-5 antibody demonstrated that IL-5 plays an im portant role in the induction of eosinophilia in mice para sitized with N. brasiliensis [6,7], However, a possible pro tective role of eosinophils in hosts infected with N. brasi liensis has not yet been confirmed.…”
mentioning
confidence: 99%